Human Papilloma Virus (HPV) driven oropharyngeal cancer in current or previous heavy smokers: should we look for a different treatment paradigm? - Lorini, Luigi; Bossi, Paolo; Psyrri, Amanda; Bonomo, Pierluigi (Frontiers in Oncology, 2024)
Human papillomavirus Virus (HPV)-associated oropharyngeal squamous cell carcinoma (OSCC) has increased in incidence in recent decades and represents a heterogeneous disease entity in the context of Head and Neck Squamous Cell Carcinoma (HNSCC), in terms of disease prognosis.Treatment of locoregionally advanced OSCC is mainly based on concurrent chemoradiotherapy.Given the younger age of patients, if compared with HPV-negative counterparts, and the high cure rates, the acute-and long-term toxicity in survivors represents a field of interest. However, patient selection for de-escalation trials remains a major challenge due to the lack of robust validated prognostic indicators within the HPV-associated OSCC.The impact of smoking status on HPV-associated OSCC prognosis has been demonstrated in the majority of studies. However, the magnitude of the association is unclear due to variability in smoking metrics and study outcomes. Smoking status has been identified as a potential confounding factor in HPV-positive de-escalation trials. Smokers with HPV-positive OSCC have a worse prognosis in most studies than non-smokers and may require different and more aggressive therapeutic strategies.